PENGGUNAAN OTOLITH UNTUK PENENTUAN UMUR DAN LAJU PERTUMBUHAN YUWANA IKAN RED DEVIL (Amphilophus labiatus) DI WADUK SERMO - , SITTY AINSYAH HABIBIE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to determined the age, spawning time, and daily growth rate of red devil (Amphilophus labiatus) juvenile based on the observation of the daily ring of fish otolith. The sampling was conducted from October 2013 to March 2014. Juvenile was collected beweekly using a hapa with 2 mm mesh size and scoop net with 1 mm mesh size. All samples were collected, and then transfered to laboratory for identification. Individual red devil was measured their length, then otolith was collected, only thirty samples used for oberservation the otolith if all samples to much. To know the first formation of daily ring, the brood stock of Tilapia (Oreochromis sp.) was spawned. Otolith was taken by immersing the fish using a 5.25% NaOCl solution. The left otolith was mounted on a glass object with buheler cement. Daily ring in otolith was observed under student microscope with 100-400x magnification and counted. Data recorded total length, diameter, and the number of daily ring. Age was determined base on the number of daily ring plus the first time of forming ring, spawning time was determined by back calculation of the sampling time plus age and incubation period. The result showed that the ring of otolith was formed on the third day after hatching and the forming of the ring was daily. Red devil was spawned coinceded with high intensity of rainfalls and new moon phase. The daily growth rate of larvae ranged 0.27-0.36 mm/day and the highest was in December.